Understanding Analysis Macroscopic, microscopic, and Acid-Base Titration Symbolic Student Class XI Science High School and Improvement Efforts Microscopy Approach - Putu Indrayani (Pascasarjana Universitas Negeri Malang (UM), 2013)
Analisis Pemahaman Makroskopik, Mikroskopik, dan Simbolik Titrasi Asam-Basa Siswa Kelas XI IPA SMA serta Upaya Perbaikannya dengan Pendekatan Mikroskopik Abstract: This study aims to determine: (1) the level of understanding of the macroscopic, microscopic and symbolic students; (2) the error understanding of macroscopic, microscopic and symbolic students; (3) the effectiveness of the microscopic approach in an effort to improve students' ability to solve the problems macroscopic, symbolic and microscopic material acid-base titration. This research uses descriptive research design and quasi-experimental research design. Data research is the understanding of macroscopic, symbolic and microscopic students on the material acid-base titration. Student comprehension test measured with instruments that include: (1) macroscopic comprehension tests, (2) test the understanding of symbolic, and (3) understanding of the microscopic tests. Content validity was tested by a team of experts and the reliability of test questions macroscopic and microscopic calculated using the Spearman-Brown while reliability symbolic test item was calculated using Cronbach's Alpha. Data were analyzed using descriptive analysis and statistical tests using Anacova. Results of the study are as follows. (1) The level of understanding of the macroscopic students is high, while the symbolic and microscopic levels of understanding of students is very low. (2) Errors identified macroscopic understanding is that students do not understand that the color shown by indicators related to the nature of the solution. Symbolic understanding of the identified errors are: (i) the student can not write ionization reaction; and (ii) students can not choose the formula used to calculate the pH of the solution. Errors identified microscopic understanding is that students can not provide a microscopic picture of a solution of a strong acid, strong base, weak acid, weak base, and salt solutions because they do not understand ionization occurs. (3) a microscopic approach resulted in an increase in the ability of students to solve problems macroscopic, symbolic and microscopic higher than conventional approaches. (4) The most important finding in this study is the students thought that the new salts can be formed if the number of moles of acids and bases react the same mole. Key Words: representation, macroscopic, microscopic, symbolic, microscopic approach Abstrak: Penelitian ini bertujuan untuk mengetahui: (1) tingkat pemahaman makroskopik, mikroskopik dan simbolik siswa; (2) kesalahan pemahaman makroskopik, mikroskopik dan simbolik siswa; (3) keefektifan pendekatan mikroskopik sebagai upaya untuk meningkatkan kemampuan siswa dalam menyelesaikan soal-soal makroskopik, simbolik dan mikroskopik pada materi titrasi asam-basa. Penelitian ini menggunakan rancangan penelitian deskriptif dan rancangan penelitian eksperimen semu. Data penelitian adalah pemahaman makroskopik, simbolik dan mikroskopik siswa pada materi titrasi asam-basa. Pemahaman siswa diukur dengan instrumen tes yang meliputi: (1) tes pemahaman makroskopik, (2) tes pemahaman simbolik, dan (3) tes pemahaman mikroskopik. Validitas isi diuji oleh tim ahli dan reliabilitas soal tes makroskopik dan mikroskopik dihitung menggunakan Spearman-Brown sedangkan reliabilitas soal tes simbolik dihitung menggunakan Alpha Cronbach’s. Data yang diperoleh dianalisis dengan menggunakan analisis deskriptif dan uji statistik menggunakan Anacova. Hasil penelitian adalah sebagai berikut. (1) Tingkat pemahaman makroskopik siswa adalah tinggi, sedangkan tingkat pemahaman simbolik dan mikroskopik siswa adalah sangat rendah. (2) Kesalahan pemahaman makroskopik yang teridentifikasi adalah siswa tidak memahami bahwa warna yang ditunjukkan oleh indikator berhubungan dengan sifat larutan. Kesalahan pemahaman simbolik yang teridentifikasi adalah: (i) siswa tidak dapat menulis reaksi ionisasi; dan (ii) siswa tidak dapat memilih rumus yang digunakan untuk menghitung pH larutan. Kesalahan pemahaman mikroskopik yang teridentifikasi adalah siswa tidak dapat memberikan gambaran mikroskopik dari larutan asam kuat, basa kuat, asam lemah, basa lemah, dan larutan garam karena mereka tidak memahami ionisasi yang terjadi. (3) Pendekatan mikroskopik menghasilkan peningkatan kemampuan siswa dalam menyelesaikan soal-soal makroskopik, simbolik dan mikroskopik lebih tinggi dibandingkan pendekatan konvensional. (4) Temuan terpenting dalam penelitian ini adalah siswa beranggapan bahwa garam baru dapat terbentuk jika jumlah mol asam dan mol basa yang bereaksi sama.Kata kunci: representasi, makroskopik, mikroskopik, simbolik, pendekatan mikroskopik